1990
DOI: 10.1038/345736a0
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary spherocytosis associated with deletion of human erythrocyte ankyrin gene on chromosome 8

Abstract: Hereditary spherocytosis (HS) is one of the most common hereditary haemolytic anaemias. HS red cells from both autosound dominant and recessive variants are spectrin-deficient, which correlates with the severity of the disease. Some patients with recessive HS have a mutation in the spectrin alpha-2 domain (S.L.M. et al., unpublished observations), and a few dominant HS patients have an unstable beta-spectrin that is easily oxidized, which damages the protein 4.1 binding site and weakens spectrin-actin interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
2
5

Year Published

1991
1991
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(94 citation statements)
references
References 32 publications
4
83
2
5
Order By: Relevance
“…In contrast, the high efficiency of nonisotopic in situ hybridization with cloned genomic DNA fragments permits such an analysis not only on metaphase chromosomes, but also in interphase nuclei. The usefulness of this approach has been demonstrated for detecting a deletion of the ankyrin gene resulting in a subtype of hereditary spherocytosis [158] as well as for the demonstration of the carrier Status of women with deletions in the dystrophin gene [159]. Diagnostic applications for other genetic diseases including microdeletions, such as retinoblastoma, DiGeorge's Syndrome, or the 4p-minus Syndrome, can be predicted.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In contrast, the high efficiency of nonisotopic in situ hybridization with cloned genomic DNA fragments permits such an analysis not only on metaphase chromosomes, but also in interphase nuclei. The usefulness of this approach has been demonstrated for detecting a deletion of the ankyrin gene resulting in a subtype of hereditary spherocytosis [158] as well as for the demonstration of the carrier Status of women with deletions in the dystrophin gene [159]. Diagnostic applications for other genetic diseases including microdeletions, such as retinoblastoma, DiGeorge's Syndrome, or the 4p-minus Syndrome, can be predicted.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Painting of whole chromosomes using DNA libraries from sorted chromosomes provides the advantage that translocations involving any material from the painted chromosome can be detected. CISS hybridization of appropriate cosmid or YAC clones may be used for the identification of still smaller translocations, deletions, or inversions, as well as for the precise definition of breakpoints [11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent assignment of the ANK-1 gene to chromosome 8 [32] suggested that abnormalities of ankyrin, might be important in a subset of HS patients. Ankyrin defects have now been described in a number of HS patients, including the recessive case mentioned above [60], a kindred with a deletion of chromosome 8 resulting in decreased dosage of the ANK-1 gene [26], and a large three-generation HS kindred where the ANK-1 gene was closely linked with the disorder [61]. Most of these cases are due to ankyrin deficiency resulting from aberrant transcription.…”
Section: Role Of Ankyrin In Diseasementioning
confidence: 99%
“…Ankyrin, is the major product of the ANK-1 gene locus which has been mapped to chromosome 8pll [26]. When proteins of the red cell membrane are separated by SDS/ PAGE, ankyrin, appears as a major polypeptide of 206 kDa followed by a ladder of minor ankyrin-related polypeptides, the principal having a molecular mass of 186 kDa [9].…”
Section: Ankyrinmentioning
confidence: 99%
See 1 more Smart Citation